Macroeconomic Dynamics and Credit Risk: A Global Perspective - Til Schuermann; Björn-Jakob Treutler; Scott M. Weiner; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2003)
We develop a framework for modeling conditional loss distributions through the introduction of risk factor dynamics. Asset value changes of a credit portfolio are linked to a dynamic global macroeconometric model, allowing macro effects to be isolated from idiosyncratic shocks. Default probabilities are driven primarily by how firms are tied to business cycles, both domestic and foreign, and how business cycles are linked across countries. The model is able to control for firm-specific heterogeneity as well as generate multi-period forecasts of the entire loss distribution, conditional on specific macroeconomic scenarios.
Keywords: 330; risk management; economic interlinkages; loss forecasting; default correlation